Сучасні погляди на геологічну будову складчастої споруди Карпат та перспективи освоєння нових вуглеводневих покладів - Лозиняк, П.Ю.; Місюра, Я.Б. (Геодинаміка, 2009)
In the paper the questions of structural-arc structure of Central (Internal) and overthrust – External Carpathians, linkage with different tectonic elements of East European platform have been considered. The important moment during the detailization of geological structure of Carpathians orogen was picking out Under-Carpathian riftogen and the determination of paraautochthone Yasynskyi element under Skolivskyi cover according to the results of gravimetrical and seismic researches. The sufficient large prospects of oil-gas-bearing owing to exposure and tracing of the new South zone of deep folds. Besides this rifting absorbed for itself main overlap masses of flysch and molassa formations and it defined the modern arched form of orogen. The perspectives of searches of hydrocarbon deposits in allochtonic complex are because of normal anticlinal folds, tectonic and lithologic screened blocks of separate fold-slices, and also as a new direction – the discovery of presurface underthrust fault structure.